Perbandingan Efikasi Beberapa Kombinasi Antiretroviral pada Pasien HIV/AIDS ditinjau dari Kenaikan Jumlah CD4 Rata-Rata (Analisis Data Rekam Medis Di RSK Dharmais Jakarta Tahun 2005 – 2006) - Rahmadini, Yulian; Andrajati, Retnosari; Andalusia, Rizka (UI Scholars Hub, 2008)
Dharmais Cancer Hospital is one of 237 hospital appointed by the government of Indonesia to give treatment, support and ARV therapy for HIV/AIDS patients. Ev-ery year, there is a significant increasing number of HIV/AIDS patients in Dharmais Cancer Hospital, therefore successfully of therapy is needed to be carried out regularly for the optimum result to the patients. One of methods to evaluating therapy is by reviewing efficacy of ARV combinations toward escalation of immunity respond (es-calation of CD4). The ARV combinations give a good efficacy if increasing CD4 > 50 cell/mm3. The objective of this study was to know the efficacy of four ARV combina-tion (each type consists of two Nucleosides Reverse Transcriptase Inhibitor and one Non-Nucleosides Reverse Transcriptase Inhibitor) base on increasing CD4 mean HIV/AIDS patients after 6 – 12 months treatment in Dharmais Cancer Hospital from 2005 – 2006, and to compare the efficacy of four ARV combinations. The four ARV combinations are combination I (Lamivudin + Zidovudin + Efavirenz), combina-tions II (Lamivudin + Zidovudin + Nevirapin), combination III (Lamivudin + Stavudin + Efavirenz), and combination IV (Lamivudin + Stavudin + Nevirapin). This study was analytical, cross-sectional design. Samples for this study were taken by total sampling using all data of HIV/AIDS patients in Dharmais Cancer Hospital from the year 2005 – 2006. The inclusion criteria were patients of fifteen years of age or more, baseline count CD4 < 200 cell/mm3, received ARV treatment for 6 – 12 months, received treatment of either one of the four ARV combination, and had data of CD4 from laboratory result before and after the treatment. Data were taken from patients’ medical record and analyzed with ANOVA-test. The result of this study from 151 patients showed that all the four combinations gave good efficacy based on the increasing CD4 mean. There was a significant difference increasing CD4 mean to HIV/AIDS patients between those received ARV combination II and those received ARV combination III (p value = 0,032). And there was not a significant difference for the other combinations. This study was from the four ARV combinations gave two the best efficacy are combination II and combination III.